Structural optimization and de novo design of dengue virus entry inhibitory peptides. - Joshua M Costin; Ekachai Jenwitheesuk; Shee-Mei Lok; Elizabeth Hunsperger; Kelly A Conrads; Krystal A Fontaine; Craig R Rees; Michael G Rossmann; Sharon Isern; Ram Samudrala; Scott F Michael (Public Library of Science (PLoS), 2010)
Viral fusogenic envelope proteins are important targets for the development of inhibitors of viral entry. We report an approach for the computational design of peptide inhibitors of the dengue 2 virus (DENV-2) envelope (E) protein using high-resolution structural data from a pre-entry dimeric form of the protein. By using predictive strategies together with computational optimization of binding "pseudoenergies", we were able to design multiple peptide sequences that showed low micromolar viral entry inhibitory activity. The two most active peptides, DN57opt and 1OAN1, were designed to displace regions in the domain II hinge, and the first domain I/domain II beta sheet connection, respectively, and show fifty percent inhibitory concentrations of 8 and 7 microM respectively in a focus forming unit assay. The antiviral peptides were shown to interfere with virus:cell binding, interact directly with the E proteins and also cause changes to the viral surface using biolayer interferometry and cryo-electron microscopy, respectively. These peptides may be useful for characterization of intermediate states in the membrane fusion process, investigation of DENV receptor molecules, and as lead compounds for drug discovery.